Optical and mechanical studies on L-Methioninium picrate NLO single crystal. (2019) - Ramesh, G.; Venkatesan, A.; Inmozhi, C.; Raja Saravanan, M.E.; Uthrakumar, R.
Abstract: Single crystals of L-Methioninium picrate (LMP) were obtained by evaporation of aqueous solution containing equimolar quantities of each component. L-Methioninium picrate crystallizes in the monoclinic system space group P21 . A single-crystal X-ray diffraction study has been carried out to confirm the identity of the crystal. Optical absorption studies on these samples reveal the minimum absorption region to be well suited for NLO applications. The mechanical strength of the grown crystal has been studied using Vicker's microhardness tester. Low dielectric loss shows that the grown crystal contains lesser defects authenticating the suitability of the crystal towards device applications.